2018
DOI: 10.3389/fphar.2018.00858
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorates Blood-Spinal Cord Barrier Disruption and Improves Functional Recovery by Inhibiting Endoplasmic Reticulum Stress-Dependent Autophagy

Abstract: Spinal cord injury (SCI) induces the disruption of blood-spinal cord barrier (BSCB), which elicits neurological deficits by triggering secondary injuries. Hydrogen sulfide (H2S) is a gaseous mediator that has been reported to have neuroprotective effect in the central nervous system. However, the relationship between H2S and BSCB disruption during SCI remains unknown. Therefore, it is interesting to evaluate whether the administration of NaHS, a H2S donor, can protect BSCB integrity against SCI and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…In recent years, it has been found that autophagy is closely related to the protective effect of H 2 S. Pretreatment with NaHS could alleviate acute myocardial ischemia injury by suppressing autophagy under oxidative stress, significantly reducing brain damage and preserving the blood-brain barrier integrity after traumatic brain injury by inhibiting autophagy via activation of the PI3K/Akt/mTOR signaling pathway and mitigating acrylonitrile-induced decrease of cell viability through influencing autophagy (Bai et al, 2018; Xu et al, 2018; Yang et al, 2018). Exogenous H 2 S also might protect mouse kidney against unilateral ureteral obstruction by suppressing ROS-AMPK-mediated autophagy, ameliorating blood-spinal cord barrier disruption and improving functional recovery by suppressing endoplasmic reticulum stress-mediated autophagy and inducing the apoptosis of hepatocellular carcinoma cells through promoting autophagy via the PI3K/AKT/mTOR signaling pathway (Chen et al, 2018a,b; Wang et al, 2017, 2018). Autophagy has also been reported to be closely related to NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been found that autophagy is closely related to the protective effect of H 2 S. Pretreatment with NaHS could alleviate acute myocardial ischemia injury by suppressing autophagy under oxidative stress, significantly reducing brain damage and preserving the blood-brain barrier integrity after traumatic brain injury by inhibiting autophagy via activation of the PI3K/Akt/mTOR signaling pathway and mitigating acrylonitrile-induced decrease of cell viability through influencing autophagy (Bai et al, 2018; Xu et al, 2018; Yang et al, 2018). Exogenous H 2 S also might protect mouse kidney against unilateral ureteral obstruction by suppressing ROS-AMPK-mediated autophagy, ameliorating blood-spinal cord barrier disruption and improving functional recovery by suppressing endoplasmic reticulum stress-mediated autophagy and inducing the apoptosis of hepatocellular carcinoma cells through promoting autophagy via the PI3K/AKT/mTOR signaling pathway (Chen et al, 2018a,b; Wang et al, 2017, 2018). Autophagy has also been reported to be closely related to NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…1C). The TJ and AJ proteins between SCMECs maintain the barrier function of BSCB, and their loss is directly related to increased permeability [30]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The intensity, timing and regulating mechanisms underlying autophagy may have protective effects or may aggravate damage in cells ( 20 , 51 ). At present, it is recognized that autophagy is increased following SCI ( 52 , 53 ). However, it has been demonstrated by various studies that the same interference may lead to different outcomes ( 18 ).…”
Section: Discussionmentioning
confidence: 99%